Two-year results of Preserflo Microshunt use in Open-angle Glaucoma Surgery - Fialová, Veronika; Váša, Martin; Rozsíval, Pavel; Kalinová, Jitka; Studnička, Jan (Ceska a slovenska oftalmologie, 2025)
AIM: To evaluate the safety and efficacy outcomes of PRESERFLO™ MicroShunt implantation in patients with primary open-angle glaucoma. MATERIAL AND METHODS: Retrospective data analysis of 19 eyes of 12 patients, comprising 5 females and 7 males. The patients underwent surgery between August 2020 and February 2022. The follow-up period was 24 months after surgery. During the follow-up period, intraocular pressure (IOP), the need to apply topical antiglaucoma medication and its spectrum, visual field status, optic nerve target findings and postoperative complications were recorded. The indication for PRESERFLO™ MicroShunt implantation was primary open angle glaucoma (POAG), poorly controlled with maximum tolerated medical therapy. RESULTS: Average IOP was reduced from 19.05 ±5.58 mmHg preoperatively to 11.47 ±2.48 mmHg at 3 months postoperatively, 12.26 ±2.48 mmHg at 6 months postoperatively, 14.0 ±2.43 mmHg at 12 months postoperatively, 11.78 ±2.37 mmHg at 18 months postoperatively, and 12.73 ±2.51 mmHg at 24 months postoperatively (p.
Keywords: drenážní implantáty glaukomové; retrospektivní studie; minimally invasive glaucoma surgery; Humans; lidé; Intraocular Pressure; Retrospective Studies; lidé středního věku; Treatment Outcome; primary open-angle glaucoma; Middle Aged; Female; Male; Glaucoma, Open-Angle; výsledek terapie; glaukom s otevřeným úhlem; mužské pohlaví; Aged; Glaucoma Drainage Implants; intraocular pressure; ženské pohlaví; nitrooční tlak; Preserflo MicroShunt; senioři